Text Book of Peripheral Nervous System - Rajani Singh; Kavita Gupta (Text Book of Peripheral Nervous System, 2022)
Nervous system is very complex and provide mechanism enabling living organism to react to changing external and internal environment. Any change in environment acts as stimulus reaching the nervous system via sensory pathway. Nervous system is divided into central nervous system and peripheral nervous system. Cranial, spinal nerves and autonomic system constitute the peripheral nervous system. In this book attempt is being is made to place all information related to peripheral nervous system at one place.